β-Galactosidase at the membrane–water interface: a case of an active enzyme with non-native conformation - Sanchez, Julieta Maria (2013)
Previously we demonstrated that Escherichia coli beta-galactosidase (β-Gal) binds to zwitterionic lipid membranes improving its catalytic activity. To understand the activation mechanism from the protein perspective, here the thermal dependence of the catalytic activity was evaluated in conjunction with parameters derived from spectroscopy and calorimetry, in the presence and absence of egg-yolk phosphatidylcholine vesicles. In solution, the native state of β-Gal exhibits a loose conformation according to the λmax of fluorescence emission, which is in the upper end of the emission range for most proteins. A non-two state thermal unfolding mechanism was derived from DSC experiments and supported by the sequential unfolding temperatures exhibited by fluorescence (55°C) and CD (60°C) spectroscopies. Quenching of β-Gal's intrinsic fluorescence, provided evidence for a novel and even looser folding for the lipid-bound protein. However, DSC data showed that the thermal unfolding in the presence of lipids occurred with a significant decrease in ΔH compared to what happened in solution, suggesting that only the population of non-bound protein molecules were involved in this process. Concluding, upon binding to a lipid-water interface β-Gal becomes trapped in a partially unfolded state, more active than that of the native protein in solution.